Vasculitis Associated With Tumor Necrosis Factor-α Inhibitors - Sokumbi, Olayemi (Mayo Foundation, 2012)
OBJECTIVE: To describe the clinical characteristics, histopathologic features, and outcomes of patients in whom vasculitis developed in association with use of tumor necrosis factor-α (TNF-α) inhibitors. PATIENTS AND METHODS: This is a retrospective review of patients evaluated at Mayo Clinic, Rochester, Minnesota, from January 1, 1998, through March 31, 2011, with a diagnosis of vasculitis induced by anti–TNF-α therapy. RESULTS: Of 8 patients with vasculitis associated with anti–TNF-α therapy (mean age, 48.5 years), 6 (75%) were female. Four (50%) had rheumatoid arthritis, 1 (13%) had Crohn disease, and 3 (38%) had ulcerative colitis. Five (63%) were treated with infliximab, 2 (25%) with etanercept, and 1 (13%) with adalimumab. The mean duration of treatment before development of vasculitis was 34.5 months. The skin was the predominant organ affected (5 patients [63%]), with the most common cutaneous lesion being palpable purpura (4 of 5 [80%]). Two organs involved in systemic vasculitis were the peripheral nervous system (4 patients [50%]) and kidney (1 patient [13%]). All cases of vasculitis were histopathologically confirmed. Seven of 8 patients improved with discontinuation of therapy (mean time to resolution, 6.9 months) and adjuvant treatment (all 8 received prednisone; another agent was also used in 7); rechallenge with anti–TNF-α therapy was not attempted in any patient. At last follow-up, no patients had experienced a recurrence of vasculitis after therapy discontinuation. CONCLUSION: Cutaneous small-vessel vasculitis was the most common finding, but systemic vasculitis, including peripheral nerve and renal vasculitis, was also frequently observed.